Politics the key concepts - Harrison, Lisa 1968-; Little, Adrian 1969-; Lock, Edward (Routledge key guides, 2015)
Politics: The Key Concepts is an up-to-date and broad-ranging introduction to the terms that lie at the heart of political discourse. Entries are drawn from areas such as political theory, international politics, political science and methodology. As well as explaining core, established principles, this informative guide explores some of the more complex, topical and contested concepts from the world of politics. In an accessible A-Z format with helpful cross-referencing and suggestions for further reading, this is a valuable reference for all students of politics, international relations and related courses